2006
DOI: 10.1021/je050462y
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of Aqueous Blends of Three Alkanolamines:  N-Methyldiethanolamine, Diethanolamine, and 2-Amino-2-methyl-1-propanol in the Range of (303 to 343) K

Abstract: Experimental values of the density and viscosity for aqueous solutions of three alkanolamines composed of 32.5 mass % N-methyldiethanolamine (MDEA) and 12.5 mass % diethanolamine (DEA) with 2, 4, 6, 8, and 10 mass % 2-amino-2-methyl-1-propanol (AMP) have been determined in the temperature range of (303.15 to 343.15) K. The experimental results of the density and viscosity are given as a function of both temperature and AMP concentration. In the range of temperature studied, the experimental density values of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
3
53
0
Order By: Relevance
“…In addition it has been reported that (aqueous) AMP is easier to regenerate compared to primary and secondary amines [2][3][4] and that aqueous solvent systems containing blended amines require lower energy during regeneration when AMP is a component. Thus, many reports on the physical properties of aqueous AMP [5][6][7][8] and aqueous amine blends containing AMP [9][10][11][12][13] that are deemed useful in the design of processes and equipment systems for CO 2 absorption have been made available in the technical literature. Likewise, data on (vapour + liquid) equilibria [14][15][16] and kinetics [17,18] and mass transport [19][20][21][22] of CO 2 absorption in blended alkanolamines containing AMP have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been reported that (aqueous) AMP is easier to regenerate compared to primary and secondary amines [2][3][4] and that aqueous solvent systems containing blended amines require lower energy during regeneration when AMP is a component. Thus, many reports on the physical properties of aqueous AMP [5][6][7][8] and aqueous amine blends containing AMP [9][10][11][12][13] that are deemed useful in the design of processes and equipment systems for CO 2 absorption have been made available in the technical literature. Likewise, data on (vapour + liquid) equilibria [14][15][16] and kinetics [17,18] and mass transport [19][20][21][22] of CO 2 absorption in blended alkanolamines containing AMP have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the uncertainty reported in this work was always determined with a 95% confidence for the best values of density experimentally determined. The estimated combined uncertainty for the experimental density values of this work is ±0.01% (±0.06 to ±0.08 kg m −3 ) [25].…”
Section: Densitymentioning
confidence: 76%
“…The temperature was controlled within ±0.002 K using a Haake A80 bath-circulator and measured with a digital thermometer, Hewlett Packard 2804 A, using a quartz sensor with a precision of ±0.001 K. The readings from this thermometer were compared with those from a calibrated thermometer Hart Scientific, 1529 Chub-E4 model whose accuracy of ±0.005 K is traceable to the US NIST. The details on the calibration of the densimeter together with the experimental procedure have been included in several previous works [21][22][23][24][25]. The reported density results for each saturated liquid phase were obtained from the average period of vibration, which was in turn obtained from at least 20 stable measurements, whose average standard deviation was ±0.0005.…”
Section: Densitymentioning
confidence: 99%
“…These experimental data of pure compound and comparisons with the literature reviews [33][34][35] were presented in Table 3. There is a good agreement between the measured densities of pure MDEA in this work, Rebolledo-Libreros and Trejo [33] and Zhao et al [34] with an average absolute deviation of 0.20%.…”
Section: Validation Of Datamentioning
confidence: 99%
“…These experimental data of pure compound and comparisons with the literature reviews [33][34][35] were presented in Table 3. There is a good agreement between the measured densities of pure MDEA in this work, Rebolledo-Libreros and Trejo [33] and Zhao et al [34] with an average absolute deviation of 0.20%. Meanwhile, the viscosities of pure MDEA obtained in this work is in agreement with those reported by Zhao et al [34] and Bernal-Garcia et al [35] with average deviation of AE0.05%.…”
Section: Validation Of Datamentioning
confidence: 99%